Review of the genus Parerigone Brauer (Diptera: Tachinidae) with five new species from China - Wang, Qiang; Zhang, Chuntian; Wang, Xinhua (Zootaxa, 2015)
The genus Parerigone (Diptera, Tachinidae) is reviewed. Five new species from China, P. atrisetosa sp. nov., P. flava sp. nov., P. flavisquama sp. nov., P. laxifrons sp. nov. and P. wangi sp. nov., are described and illustrated. Parerigone flavihirta (Chao & Sun) is proposed as a new synonym of P. takanoi Mesnil. Diagnosis of species examined and a key to the 15 species of Parerigone are provided.